Diptera diversity : status, challenges and tools - Pape, Thomas; Bickel, Daniel J.; Meier, Rudolf, 1963- (Brill, 2009)
This is the first comprehensive synopsis of the biodiversity of Diptera, with chapters on all regional faunas, Diptera as ecological indicators, statistical techniques for estimating species diversity based on the known fauna, molecular tools and trends in digital publication.